Unlocking the potential of TIPS placement as a bridge to elective and emergency surgery in cirrhotic patients: a meta-analysis and future directions for endovascular resuscitation in acute care surgery - Ramiro Manzano-Nunez; Alba Jimenez-Masip; Julian Chica-Yanten; Abdelaziz Ibn-Abdelouahab; Massimo Sartelli; Nicola de’Angelis; Ernest E. Moore; Alberto F. García (World Journal of Emergency Surgery, 2023)
Abstract Background In this systematic review and meta-analysis, we examined the evidence on transjugular intrahepatic portosystemic shunt (TIPS) as a bridge to elective and emergency surgery in cirrhotic patients. We aimed to assess the perioperative characteristics, management approaches, and outcomes of this intervention, which is used to achieve portal decompression and enable the safe performance of elective and emergent surgery. Methods MEDLINE and Scopus were searched for studies reporting the outcomes of cirrhotic patients undergoing elective and emergency surgery with preoperative TIPS. The risk of bias was evaluated using the methodological index for non-randomized studies of interventions, and the JBI critical appraisal tool for case reports. The outcomes of interest were: 1. Surgery after TIPS; 2. Mortality; 3. Perioperative transfusions; and 4. Postoperative liver-related events. A DerSimonian and Laird (random-effects) model was used to perform the meta-analyses in which the overall (combined) effect estimate was presented in the form of an odds ratio (summary statistic). Results Of 426 patients (from 27 articles), 256 (60.1%) underwent preoperative TIPS. Random effects MA showed significantly lower odds of postoperative ascites with preoperative TIPS (OR = 0.40, 95% CI 0.22–0.72; I2 = 0%). There were no significant differences in 90-day mortality (3 studies: OR = 0.76, 95% CI 0.33–1.77; I2 = 18.2%), perioperative transfusion requirement (3 studies: OR = 0.89, 95% CI 0.28–2,84; I2 = 70.1%), postoperative hepatic encephalopathy (2 studies: OR = 0.97, 95% CI 0.35–2.69; I2 = 0%), and postoperative ACLF (3 studies: OR = 1.02, 95% CI 0.15–6.8, I2 = 78.9%). Conclusions Preoperative TIPS appears safe in cirrhotic patients who undergo elective and emergency surgery and may have a potential role in postoperative ascites control. Future randomized clinical trials should test these preliminary results.